2007
DOI: 10.1128/jb.00592-06
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sulfur Assimilation Pathways in Burkholderia cenocepacia : Identification of Transcription Factors CysB and SsuR and Their Role in Control of Target Genes

Abstract: Two genes encoding transcriptional regulators involved in sulfur assimilation pathways in Burkholderia cenocepacia strain 715j have been identified and characterized functionally. Knockout mutations in each of the B. cenocepacia genes were constructed and introduced into the genome of 715j by allelic replacement. Studies on the utilization of various sulfur sources by 715j and the obtained mutants demonstrated that one of the B. cenocepacia regulators, designated CysB, is preferentially involved in the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…These findings imply that O-acetylserine does not affect the nature of DNA binding of CysB DS1 . In previous studies, the function of CysB of Burkholderia cenocepacia appeared to be independent of the presence of O-acetylserine (16); therefore, CysB may vary with respect to the recognition of an inducer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings imply that O-acetylserine does not affect the nature of DNA binding of CysB DS1 . In previous studies, the function of CysB of Burkholderia cenocepacia appeared to be independent of the presence of O-acetylserine (16); therefore, CysB may vary with respect to the recognition of an inducer.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of SfnR implied that sulfone utilization of DS1 is controlled by a novel mechanism for the sulfate starvation response because all of the other known transcriptional regulators of gram-negative bacteria involved in organosulfur metabolism belong to the LysR family, e.g., Cbl and SdsB (5), AsfR (40), SftR (18), and SsuR (16). More interestingly, SfnR lacks an N-terminal regulatory domain, unlike many other 54 -dependent transcriptional regulators (8,9).…”
mentioning
confidence: 99%
“…B. cenocepacia strains used in this study are shown in Table 1. Growth conditions were essentially the same as those described previously (18). The modified sulfur-free M9 medium was supplemented with the alternative sole sulfur sources listed in Table 2, used at a concentration of 0.25 mM (sodium salts) each or 0.1 mM for L-cystine or L-methionine.…”
Section: Methodsmentioning
confidence: 99%
“…We noticed that the functions of B. cenocepacia CysB and SsuR may partially replace each other in the regulation of some target promoters, e.g., sbp P and cysI P (controlling expression of the sbp cysTWA operon encoding the sulfate transporter and the cysIXHD 1 NG operon encoding sulfate activation and reduction functions, respectively). One example of a B. cenocepacia promoter upregulated specifically by SsuR was identified as ssuD P , preceding the ssuDBC cluster that encodes aliphatic sulfonate transport and desulfonation functions (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation